The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.7717/peerj.4024
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of CO2 leakage on the soil bacterial community in a simulated gas leakage scenario

Abstract: The technology of carbon dioxide (CO2) capture and storage (CCS) has provided a new option for mitigating global anthropogenic emissions with unique advantages. However, the potential risk of gas leakage from CO2 sequestration and utilization processes has attracted considerable attention. Moreover, leakage might threaten soil ecosystems and thus cannot be ignored. In this study, a simulation experiment of leakage from CO2 geological storage was designed to investigate the short-term effects of different CO2 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…This suggested that Acidobacteria was significantly correlated with the soil pH value. Ma et al [40] have reported similar results, that is, the abundance of Acidobacteria changed with variations in the soil pH value. In this study, this result indicated that external environmental variables affected the network interactions among different microbial groups and that such changes may be related to soil properties, such as the pH value.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This suggested that Acidobacteria was significantly correlated with the soil pH value. Ma et al [40] have reported similar results, that is, the abundance of Acidobacteria changed with variations in the soil pH value. In this study, this result indicated that external environmental variables affected the network interactions among different microbial groups and that such changes may be related to soil properties, such as the pH value.…”
Section: Discussionmentioning
confidence: 64%
“…We know that Proteobacteria is widely distributed around the world. It has an aerobic bacterium that is capable of degrading a variety of contaminants, as well as some bacteria that produces several oxidases that oxidize diverse compounds [40]. Proteobacteria has a highly diverse physiology and is distributed in almost all of the different ecological environments.…”
Section: Discussionmentioning
confidence: 99%
“…TN was determined using the semi-micro Kjeldahl method [46]. Soil AP was determined using the hydrochloric acid ammonium chloride method [47]. Soil AK was determined by caries by ammonium acetate extraction-flame photometry [46] (FP640, Jingke, Shanghai, China).…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
“…This suggested that Acidobacteria was significantly correlated with the soil pH value. Ma et al[35] have reported similar results that the abundance of Acidobacteria changed with variation in the soil pH value. In this study, this result indicated that external environmental variables affected the network interactions among different microbial groups and that such changes may be related to soil properties, such as pH value.…”
mentioning
confidence: 68%